ETHICS AS A REGULATOR OF INTERPERSONAL RELATIONS AND COMMUNICATION IN THE HUMAN RESOURCE MANAGEMENT PROCESS OF HIGHER EDUCATION INSTITUTIONS (Education in the 21st Century, 2025)
In the contemporary context of intense competition, higher education institutions face the imperative of developing a new model of management and organizational culture. This article examines the role of business communication, ethics, and etiquette as central factors for effective human resource management and the value-driven sustainability of the educational environment.The theoretical framework incorporates a comparative analysis of international experience, highlighting manifestations of ethical governance and communication culture in higher education systems. Special attention is given to universities in the United States and European Union countries, where ethics is considered not only as a behavioral regulator but also as a strategic component of educational quality assurance and human resource development. U.S. “Professional Conduct Standards” and European ethical codes exemplify models that ensure academic integrity, transparency, and accountability. Within the EU educational policy framework (EUA, Bologna Process), systematic integration of ethical and communication skills is emphasized as part of institutional management and organizational culture.The study aims to reveal international differences and propose an integrated approach for developing a national ethical management model that aligns with international standards while reflecting local educational realities. The scientific novelty lies in the creation of a systematic model combining business ethics, etiquette, and communication, linking value-based human resource management with structural stability.The findings demonstrate that without clear mechanisms for ethical governance and consistent communication policies, improvements in higher education quality, public trust restoration, and long-term competitiveness are unattainable. Harmonized development of ethical and communication factors fosters organizational culture, reduces conflicts, and enhances trust and collaboration within universities. The study recommends introducing the course “Business Communication and Ethics,” revising university ethical codes, and developing a hybrid model combining legal and value-based approaches. This article, grounded in authoritative Armenian and international sources, provides guidance for enhancing university management culture and educational quality.
Keywords: higher education institution; management culture; ethics; communication; interpersonal relations; human resource management; code of ethics